THE RELATIONSHIP BETWEEN THE COLONIZER AND THE COLONIZED IN THE BOOKS "THE CONDITIONS OF THE RENAISSANCE" BY MALEK BENNABI AND "ORIENTALISM" BY EDWARD SAID - Nabiha Hamzaoui & Amran Kaddour (Ziglôbitha)
Abstract : The research presents a comparison between Malek Bennabi's The Conditions of Renaissance and Edward Said's Orientalism, highlighting the influence of the former on the latter in analyzing the relationship between the colonizer and the colonized. The two authors intersect in their experiences, from confronting colonial occupation to writing in a Western language and migrating to the West. The study focuses on their respective perspectives on the relationship between the "self" (the colonized) and the "other" (the colonizer), illustrating how the West used cultural pretexts to justify colonialism by scientifically studying the colonized to undermine their cultural essence. The research emphasizes the continuity of colonial schemes on a cultural level even after independence and calls for similar studies to further explore this connection between the two thinkers. Such analyses would reinforce the validity of the idea and the effectiveness of proposed solutions for confronting colonialism. Keywords: self and other, colonizer, colonized, Orientalism.